Effect of different types of biochar on soil properties and functional microbial communities in rhizosphere and bulk soils and their relationship with CH4 and N2O emissions - Qi, Jian-Qing; Yuan, Hai-Yan; Zhuang, Qi-Lu; Zama, Eric-Fru; Tian, Xiao-Fei; Tao, Bao-Xian; Zhang, Bao-Hua (Frontiers in Microbiology, 2023)
Biochar as an agricultural soil amendment plays vital roles in mediating methane (CH4) and nitrous oxide (N2O) emissions in soils. The link between different types of biochar, bulk soil, and rhizosphere microbial communities in relation to CH4 and N2O emissions is being investigated in this study. The rice pot experiment was conducted using biochar at two temperatures (300°C and 500°C) in combination with three biochar levels (0, 2, 10% w/w). Soil properties and the abundance of genes associated with CH4 and N2O emissions from both rhizosphere and bulk soils were investigated. The study also aimed to examine the structure of microbial communities (pmoA, nosZ) in rhizosphere and bulk soils whereas CH4 and N2O emissions were monitored while growing rice. Results showed that biochar at 300°C and 10% incorporation significantly increased the CH4 emissions by up to 59% rise compared to the control group. Random Forest analysis revealed that the ratio of mcrA/pmoA along with the abundance of mcrA from both rhizosphere and bulk soils, the abundance of AOA, TN, DOC, and the community composition of pmoA-harboring microorganisms from both bulk and rhizosphere soils were important predictors of CH4 emissions. Therefore, the ratio of mcrA/pmoA in rhizosphere soil and the abundance of AOA in bulk soil were the main factors influencing CH4 emissions. Variation Partitioning Analysis (VPA) results indicated that the effects of these factors on bulk soil were 9% of CH4 emissions variations in different treatments, which contributed more than rhizosphere soils’ factors. Moreover, random forest analysis results indicated that the abundance of AOB in bulk soil was the most important predictor influencing N2O emissions. The VPA result revealed that the factors in rhizosphere soil could explain more than 28% of the variations in N2O emissions. Our study highlights that rhizosphere soil has a more significant effect than bulk soil on N2O production. Our findings further the understanding of the link between bulk and rhizosphere attributes, and their impact on CH4 and N2O emissions in paddy soils. In summary, we recommend the application of biochar at 500°C and 2% incorporation rate for agricultural production in the area.